COMPETENCY-BASED ASSESSMENT IN PROFESSIONAL EDUCATION: INTERNATIONAL BEST PRACTICES AND IMPLICATIONS FOR UZBEKISTAN - Mokhira Eshanova Yuldashbaevna (Bright Mind Publishing, 2026)
This article explores the assessment of learning outcomes in professional education, with a particular focus on the evolving requirements of the labor market in Uzbekistan and globally. It examines the importance of competency-based assessment in training qualified personnel, strengthening national qualification systems, and aligning education with employer expectations. The study employs a qualitative review of national policy documents, professional standards, and pedagogical approaches, complemented by a comparative analysis of international best practices from Germany, Finland, and Singapore—countries recognized for their advanced vocational education and training systems. Findings highlight that while Uzbekistan has introduced competency-based reforms, further progress is needed in strengthening employer involvement, expanding modular and workplace-based assessments, and recognizing prior and informal learning. Scholarly perspectives from both Uzbek and international researchers confirm that assessment should be dynamic, practice-oriented, and grounded in experiential learning. The discussion emphasizes that integrating international insights into local reforms can significantly enhance professional education quality and labor market responsiveness. The article concludes that competency-based assessment is a strategic necessity for Uzbekistan, providing a pathway to improved workforce readiness, stronger industry–education collaboration, and sustainable socio-economic development.
Keywords: Professional education, competency-based assessment, labor market alignment, national qualification system, vocational training, international best practices, Uzbekistan.